2016
DOI: 10.1021/acsami.6b03113
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Electronic and Ionic Conductor-Coated Cathode Material for High-Voltage Lithium Ion Battery

Abstract: A lithium ionic conductor, Li1.3Al0.3Ti1.7(PO4)3 (LATP), is introduced as a coating material on the surface of Mg-doped LiCoO2 to improve electrochemical performances for high-voltage (4.5 V) lithium ion batteries. Structure, morphology, elemental distribution, and electrical properties of the materials are thoroughly characterized by SEM, TEM, EELS, EDS, and C-AFM. The coating layer is electrically conductive with the aid of Mg ions which are used as a dopant for the active materials; therefore, this mixed el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Now that the experimental advantage of slight Ni bulk doping is obvious, we seek to understand the underlying mechanism. [24,34,35] Third, some studies of bulk doping show suppressed phase transitions yet there were no improvements in high-voltage cyclability (i.e., the case showing B but not A). The latter was also observed in the present work, as illustrated in the differential capacity versus voltage (dQ/dV) plot of the first charge/discharge curve of in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…Now that the experimental advantage of slight Ni bulk doping is obvious, we seek to understand the underlying mechanism. [24,34,35] Third, some studies of bulk doping show suppressed phase transitions yet there were no improvements in high-voltage cyclability (i.e., the case showing B but not A). The latter was also observed in the present work, as illustrated in the differential capacity versus voltage (dQ/dV) plot of the first charge/discharge curve of in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…15,[20][21][22][23]26,[28][29][30] Most studies attribute the improvements in LCO cycling performance to Mg either providing structural stability 15,21,26,27 or improving the conductivity of the material. 20,23,29,30 Recently, Shim et al reported a retention of 85% capacity after 500 cycles and 60% after 700 cycles in 2900 mAh prismatic full cells (LCO/graphite) cycling up to 4.4 V (4.48 V vs Li/Li + ) utilizing a combination of ionic conductor coating and Mg doping. …”
mentioning
confidence: 99%
“…15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] 15,[20][21][22][23]26,[28][29][30] Most studies attribute the improvements in LCO cycling performance to Mg either providing structural stability 15,21,26,27 or improving the conductivity of the material. 20,23,29,30 Recently, Shim et al reported a retention of 85% capacity after 500 cycles and 60% after 700 cycles in 2900 mAh prismatic full cells (LCO/graphite) cycling up to 4.4 V (4.48 V vs Li/Li + ) utilizing a combination of ionic conductor coating and Mg doping. 30 While much progress has been made for cycling below 4.5 V (vs. Li/Li + ), there are no studies, as far as the authors are aware of, on the long term effect of Mg doping on the O3-O6-O1 phase transitions which occur around 4.55 V and 4.63 V (vs. Li/Li + ) respectively.…”
mentioning
confidence: 99%
“…To date, the materials used as coating layer mainly include carbon materials, [44,[50][51][52] metal oxides, [22] conducting polymer, [53] and so on. Liu et al prepared Al 2 O 3 coated P2-Na 2/3 Ni 1/3 Mn 2/3 O 2 by simple wet chemistry method, which reduces the direct contact between electrode and electrolyte and alleviates side reaction.…”
Section: Surface Coatingmentioning
confidence: 99%